(untitled) (Journal of Asian Development Studies, 2014)
This paper analyses the dynamic relationship between banks’ information disclosure and depositor discipline. Signalling theory posits that the amount of information that banks disclose depends on their risk. In line with this, we model the relationship between deposit growth and information disclosure as an endogenous process. This paper investigates how depositor discipline constrains banks’ behaviour by extracting the impact of an exogenous increase in the amount of information that banks disclose on the quantity of deposits. We find that healthy banks can raise deposits by disclosing more information, while weak banks cannot. This confirms that depositor discipline encourages healthy banks to disclose more information. These findings offer support to the proposition of the third pillar of Basel II which aims to encourage market discipline through greater disclosure.